EVALUASI PENGEMBANGAN EKOWISATA MANGROVE DI DESA SEBONG LAGOI KABUPATEN BINTAN PROVINSI KEPULAUAN RIAU - Prakasa Mustanto; Syaifuddin Nasution; Dessy Yoswaty (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This study aimed to evaluate the implementation of the mangroveecotourism program that was launched and operated by the stake holders inthe Sebong Lagoi Village, Bintan regency. The method used in this studywas survey method. Program evaluation refers to the criteria or benchmark.Based on Arikunto (2008), rated 5 (very good) if there are all of indicators,rated 4 (good) if there are 3 indicators, rated 3 (normal) if there are 2indicators, rated 2 (bad) if there is only 1 indicators, rated 1 (very bad) ifthere is no indicator fulfilled. The result showed that Sebong River Tours,Fireflies Tour and Traditional Fishing Tour activity classified in goodcategory. Snorkeling activity classified in very well category. Fishing Tourand Kampoeng Tour classified in normal category. Mangrove replantingactivity classified in bad category. The main attraction of the tourists ismangrove ecotourism activity.Keywords: Evaluation, Mangrove Ecotourism, Sebong Lagoi Village